Investigating pre-professional dancer health status and preventative health knowledge - Nicholas, Joanna; Grafenauer, Sara (Frontiers in Nutrition, 2023)
Introduction: Dance is a highly demanding physical pursuit coupled with pressure to conform to aesthetic ideals. Assessment of health status and preventative health knowledge of pre-professional dancers may help inform educational strategies promoting dancers' health and career longevity. The aim of this research was to establish a baseline understanding of dance students at a single preprofessional institution based on metrics focused on current health, nutrition, lifestyle, and well-being while also gauging knowledge of longer-term health implications. Methods: Adopting a cross-sectional study design, the Dance-Specific Energy Availability Questionnaire was tailored for Australian participants and administered online. Results: The response rate was 59.5% (69/116 eligible students) and the survey was completed in full by 63 students. Mean BMI was 20 kg/m 2 , although among females, 47% had a BMI <20 (range 16 to 25 kg/m 2 ), and at their lowest reported weight BMI was 14 to 25 kg/m 2. Over a third had either experienced (31%) or were currently experiencing (3.4%) secondary amenorrhea (period absence ≥3 consecutive months). Most dancers did not exclude food groups, however, 24% had been advised to exclude particular foods in the past, mostly by dance teachers. A large percentage used nutritional supplements (68%) with 60% supplementing with iron and more than half (53%) taking two or more supplements. Only 25% had ever utilised a qualified dietitian, although 16% reported a history of eating disorders and 25% reported vegetarian or vegan eating patterns. REDs risk scores ranged from -16 to +16 points with negative scores indicating LEA and higher risk of REDs. The mean score for males was 5.2 (SD=3.9) and 2.1 (SD=5.9) for females, with 33.3% producing a negative score. Conclusion: Results provide insight to health knowledge and particular issues pertinent for dancers and highlights the need for specific education strategies to promote a preventative health focus for those entering a pre-professional program. This study also highlights the need for improved awareness of LEA and REDs among all practitioners working with dancers along with cultural and structural changes within the broader dance community to help protect and promote the well-being of dancers.